Photoacoustic resonance spectroscopy for biological tissue characterization - Gao, Fei (2015)
By “listening to photons,” photoacoustics allows the probing of chromosomes in depth beyond the optical diffusion limit. Here we report the photoacoustic resonance effect induced by multiburst modulated laser illumination, which is theoretically modeled as a damped mass-string oscillator and a resistor-inductor-capacitor (RLC) circuit. Through sweeping the frequency of multiburst modulated laser, the photoacoustic resonance effect is observed experimentally on phantoms and porcine tissues. Experimental results demonstrate different spectra for each phantom and tissue sample to show significant potential for spectroscopic analysis, fusing optical absorption and mechanical vibration properties. Unique RLC circuit parameters are extracted to quantitatively characterize phantom and biological tissues.